ANALISA KEPEMIMPINAN DI NON GOVERNMENTAL ORGANIZATION DI INDONESIA - , Yussy Agastuty ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine a map of leadership role in the Non- Governmental Organization in Indonesia . Second , from 109 respondents which comes from 37 NGOs, researcher has clasified it into 7 NGO sectors which has the same issues and similar activities . Therefore , it is important to map from the 7 sectors of the NGO, in which NGO has perceived as the most dominating leadership role . Third , it is also important to map among the 7 NGO sector groups, in which dimension of leadership has perceived as the most dominating . This research was conducted using a quantitative approach and survey methods in data collection . Descriptive analysis is done by calculating the average value ( mean score) with SPSS 17.0 . From the analysis concluded that the most dominant leadership role for NGO respondents in this study is the dimension of Politicians and campaigner because it has the highest mean score . Secondly , from the 7 NGO sector groups which is a small industry , health , education , democracy and human rights , women's empowerment , environment and anti- corruption , the NGO which has the highest mean score of leadership is with the NGO anti-corruption activities . Third, the results of the research between NGO sector groups on each dimension of leadership suggests that the NGO sector of industrial activity , health , education , democracy and human rights has the largest mean score on the dimension change agent . NGO empowerment of women , the environment and anti-corruption have the greatest mean score on the dimension of visionary and strategist . Besides that , democracy and human rights NGOs and anti- corruption NGO also has the largest mean score in the dimension Politicians and campaigner.